High 4-1BB Expression in PBMCs and Tumor Infiltrating Lymphocytes (TILs) in Patients with Head and Neck Squamous Cell Carcinoma - Bin-Alee, Fardeela; Chunthagonesupawit, Nattharee; Meesakul, Tamonwan; Diloktaweewattana, Areeya; Mahattanasakul, Patnarin; Mutirangura, Apiwat; Ruangritchankul, Komkrit; Keelawat, Somboon; Kitkumthorn, Nakarin (European Journal of Dentistry, 2023)
Objective 4-1BB is a costimulatory immune-activating molecule. Increased amounts of this protein have previously been found in the plasma of patients with oropharyngeal and oral cancer. Here, we focused on this molecule that functions as part of the immune system. We investigated 4-1BB in the peripheral blood mononuclear cells (PBMCs) and tumor infiltrating lymphocytes (TILs) of patients with head and neck squamous cell cancer (HNSCC).Materials and Methods The expression level of 4-1BB in the PBMCs was determined using real-time polymerase chain reaction (PCR). The TIMER (Tumor Immune Estimation Resource) web server was utilized to approximate the 4-1BB level in HNSCC TILs. Moreover, 4-1BB immunohistochemistry (IHC) was used to validate TILs in four organs of HNSCC, including oral cancer (OC), oropharyngeal cancer (OPC), sinonasal cancer (SNC), and laryngeal cancer (LC), in both the tumor area and adjacent normal epithelium. The difference in 4-1BB expression levels in various groups was assessed using a Kruskal-Wallis test and an independent sample t-test.Results The level of 4-1BB expression in PBMCs was highest in OPC, followed by OC and healthy controls (HC). Significant differences were discovered between HC and OPC and between OC and OPC. Bioinformatics revealed a substantial correlation between 4-1BB expression level and lymphocyte infiltration in HNSCC, including B cells, CD8+ T cells, and CD4+ T cells. IHC validation in HNSCC tissue revealed that the average number of 4-1BB positive TILs in all four HNSCC subtypes was considerably greater than the number of lymphocytes seen in adjacent normal tissue. Interestingly, the number of lymphocytes that were 4-1BB positive increased in relation to the TIL level.Conclusion A higher number of 4-1BB expression levels were found in the PBMCs and TILs of HNSCC patients, implying that 4-1BB may be a promising approach for HNSCC patients to improve their immune function. It is important to study and create a treatment that uses 4-1BB medicine as well as existing drugs.
Keywords: 4-1BB; head and neck cancer; PBMCs; TILs